Identification of Der f 23 as a new major allergen of Dermatophagoides farinae - He, Yongshen (Mol Med Rep, 2019)
House dust mites (HDM) are common allergen sources worldwide. At present, 32 of the 37 internationally recognized HDM allergen groups have been identified in Dermatophagoides farinae. The present study study describes the identification of the first known D. farinae Group 23 allergen (Der f 23). Recombinant Der f 23 protein (rDer f 23) was cloned, expressed and purified. The open reading frame of rDer f 23 was 525 base pairs and encoded a 174-amino acid protein (GenBank accession no., KU166910.1). ELISAs indicated that 72/129 HDM allergic serum samples (55.8%) had specific immunoglobulin E (sIgE) binding activity to rDer f 23. Additionally, 3/10 patients with HDM allergies (30%) exhibited positive skin prick test reactions to rDer f 23. IgE western blot analysis data suggested that only 4/11 HDM allergic sera had a positive sIgE binding result. Sequence homology analysis revealed an extra P2 region (Ser56-Thr117) in Der f 23 that was not present in the D. pteronyssinus homolog, which may affect sIgE binding. Der f 23ΔP2 demonstrated binding with HDM allergic sera, whereas the P2 peptide alone did not. The sIgE binding ability of Der f 23 ΔP2 (Der f 23 with a truncated P2 region) was more marked compared with that of Der f 23 in an IgE ELISA. These data indicate that P2 region in Der f 23 attenuates IgE binding ability. In conclusion, the results of the present study indicate that Der f 23 is a major HDM allergen with predominantly conformational sIgE binding epitopes. The allergenic identification of Der f 23 and its inclusion in World Health Organization/International Union of Immunological Societies database contributes to the theoretical basis underlying the diagnosis and treatment of HDM allergic diseases.